2019
DOI: 10.1128/aem.02878-18
|View full text |Cite
|
Sign up to set email alerts
|

Higher Temperatures Do Not Always Achieve Better Antibiotic Resistance Gene Removal in Anaerobic Digestion of Swine Manure

Abstract: This study employed high-throughput quantitative PCR and 16S rRNA sequencing to evaluate the effect of temperature and residual antibiotics on the dynamics of antibiotic resistance genes (ARGs) and microbial communities during anaerobic digestion of swine manure. The abundances of total ARGs and 16S rRNA genes significantly decreased in all of four treatments (25°C, 37°C, and 37°C with 50 mg of wet weight antibiotics of body weight, and 55°C). The abundances of most ARG types were significantly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Both the World Economic Forum [24] and the World Health Organization [25] have described antibiotic resistance as one of the major threats to humanity in the coming century. Antibiotics or their metabolites enter wastewater treatment plants (WWTPs) and subsequently end up in surface waters through the sewage system, since WWTPs were not designed to remove antibiotics [22,[26][27][28]. Not only surface waters, but soils and sediments also suffer from the accumulation of antibiotics due to the usage of veterinary antibiotics and subsequent application of contaminated manure to the soil [20][21][22]27,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Both the World Economic Forum [24] and the World Health Organization [25] have described antibiotic resistance as one of the major threats to humanity in the coming century. Antibiotics or their metabolites enter wastewater treatment plants (WWTPs) and subsequently end up in surface waters through the sewage system, since WWTPs were not designed to remove antibiotics [22,[26][27][28]. Not only surface waters, but soils and sediments also suffer from the accumulation of antibiotics due to the usage of veterinary antibiotics and subsequent application of contaminated manure to the soil [20][21][22]27,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Intensification of biogas production can be also achieved by dewatering wastewater and sewage, optimization of physicochemical parameters such as pH, temperature, HRT, size of molecules submitted to fermentation, submitted to fermentation, configuration of a bioreactor, C/N ratio, intensity of the mixing process, and by employing immobilized biofilms or biofilters …”
Section: Feedstocks Technologies and Factors Design To Intensify Bimentioning
confidence: 99%
“…Methanogenic microorganisms are highly sensitive to changes in pH in bioreactors. Excessively low pH can cause inhibition of AD, while very high pH can lead to the production of free ammonia, which is toxic to methanogenic microorganisms . The microorganisms participating in the process of methane fermentation, that is, hydrolytic, acidogenic, and methagenic microorganisms, have optimal pH ranges in which the maximum reaction efficiency is obtained.…”
Section: Feedstocks Technologies and Factors Design To Intensify Bimentioning
confidence: 99%
“…The plasmid was also found to be integrated into transposons (Cain et al 2010). Huang et al (2019) reported abundance of ARGs and transposase genes, which were decreased during anaerobic digestion of swine manure. Most ARGs including sul genes were signi cantly correlated with transposase genes.…”
Section: × × × ×mentioning
confidence: 99%
“…The authors found ARGs abundance varied among farms, and ARG concentrations generally did not correlate to average antimicrobial usage due to complex environmental factors. Most manure conditions were simulated at the bench scale, and only few analyzed commonly used practices in dairy farms (Flores-Orozco et al 2020;Huang et al 2019;Pei et al 2007;Selvam et al 2012;Sun et al 2016;Wang et al 2012). Wang et al (2012) simulated the environmental conditions of swine manure treatment by lab scale thermophilic composting and ambient temperature lagoon storage with modest aeration over a 48-day period.…”
Section: Introductionmentioning
confidence: 99%